Cloud methods electronic health services (EHS), for improving cyber security and privacy data, suggest solutions for unauthorized access issue - Raed Al-hamarneh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
in 2020 was certainly not a traditional year. The pandemic make huge pressures on cyber security, IOT, leaders and businesses were forced to rapidly accelerate their digital transformation plans and massively expand their remote working capabilities. Cyber actors seized the opportunities created by the pandemic and exploited vulnerabilities in security defenses to gain access to business networks and sensitive data. In 2020, phishing and ransomware attacks increased, as did web application attacks, according to the recently published Verizon 2021 Data Breach Investigations Report. The report provides insights into the tactics, techniques and procedures used by nation state actors and cybercriminal groups and how these changed during the pandemic. To improve the cloud security, I used very important methods, in my proposal system very secure devices that contribute to reduce or avoid for illegal access cloud computing , all medical services ,must be secure ( store , transfer). In this paper, we propose new EHS sharing framework that combines modern technology and the centralized system on a cloud platform. Particularly, we design atrustworthy access control mechanism using smart contracts to achieve secure EHRs sharing among differentpatients and medical providers